Cardiac side effects of trastuzumab in breast cancer patients – single centere experiences - Huszno, Joanna; Leś, Dominika; Sarzyczny-Słota, Danuta; Nowara, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : The aim of this study was to present our own experiences concerning risk factors for cardiac side effects in the study group. Material and methods: The study was performed in 120 patients with HER2-overexpressing breast cancer who received immunotherapy in the Clinical and Experimental Oncology Department, between 2006 and 2011. Results : LVEF reduction > 10% of the baseline fraction was observed in 10 (8%) patients. Symptomatic heart failure occurred in two individuals. Due to persistent cardiotoxicity five patients (4%) had to discontinue therapy prematurely. Risk factors for cardiac toxicity in the analyzed group included: previous radiotherapy to the left side of the chest (p = 0.05), higher BMI (p = 0.05), negative steroid receptor status (p = 0.045) and low baseline LVEF (p < 0.001). Patients receiving radiotherapy were more likely to develop cardiotoxicity if presenting older age (p = 0.0003). Conclusions : Previous radiotherapy to the left side of the chest, negative steroid receptor status, high BMI and low baseline LVEF were associated with increased risk of cardiac dysfunction. There was no difference between patients receiving adjuvant therapy and those treated due to metastatic disease.